2021
DOI: 10.1037/xge0001063
|View full text |Cite
|
Sign up to set email alerts
|

An integrated theory of deciding and acting.

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(79 citation statements)
references
References 81 publications
(150 reference statements)
7
72
0
Order By: Relevance
“…These results complement existing findings for constant FP and indicate a degree of independence between the processes of response preparation and execution [2,34,35]. Similar results were reported in the study by Servant et al [24]. Using a random dot motion task, the study found strong positive between-participant correlations (r>0.95) between the duration of the premotor period and the duration of the motor period as well as low values of the within-subject correlations (r<0.13) at different levels of complexity of the perceptual task.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…These results complement existing findings for constant FP and indicate a degree of independence between the processes of response preparation and execution [2,34,35]. Similar results were reported in the study by Servant et al [24]. Using a random dot motion task, the study found strong positive between-participant correlations (r>0.95) between the duration of the premotor period and the duration of the motor period as well as low values of the within-subject correlations (r<0.13) at different levels of complexity of the perceptual task.…”
Section: Plos Onesupporting
confidence: 91%
“…Finally, research by Servant et al [24] proposed a Dual-Threshold Diffusion Model, according to which the reaction time period is divided into premotor and motor periods based on the EMG latency. The results showed that decision making in the situation of increasing uncertainty using a random dot motion task causes an increase in the duration of both periods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a cognitive premotor planning/initiation component along with physical motor speed. That is, fractionating non-decision time, and specifically Tr , into premotor planning + motor time (Servant et al, 2021 ). We focus our manipulations and questions specifically on whether physical motor slowing is or is not captured by the drift rate ( v ) parameter.…”
Section: Present Experimentsmentioning
confidence: 99%
“…One potential method for limiting model mimicry is through constraining the models to account for additional types of data, making it increasingly difficult to successfully account for all trends in the empirical data (Servant, White, Montagnini, & Burle, 2015;Servant, Logan, Gajdos, & Evans, 2021;Evans, Dutilh, et al, 2020). Specifically, while EAMs are typically only required to account for the trends in the choice response time distributions, they can be extended to also account for other types of data (e.g., muscle movements), which may result in different underlying architectures making distinguishable joint predictions across all types of data.…”
Section: Introductionmentioning
confidence: 99%